2002
DOI: 10.1302/0301-620x.84b3.0840375
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic versus open carpal tunnel release in bilateral carpal tunnel syndrome

Abstract: The advantages and disadvantages of endoscopic compared with open carpal tunnelreleasearecontroversial. We have performed a prospective, randomised, blinded assessment in a district general hospital in order to determine if there was any demonstrable advantage in undertaking either technique. Twenty-five patients with confirmed bilateral idiopathic carpal tunnel syndrome were randomised to undergo endoscopic release by the single portal Agee technique to one hand and open release to the other. Independent pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 0 publications
3
30
0
1
Order By: Relevance
“…Both findings were supported in some of the prospective studies conducted comparing the two techniques 21,26 but not in others. [22][23][24][25] No difference in return to work data was found in some studies 23,24 despite greater short-term pain in the ECTR groups. Differences in symptom severity scores, functional status, and satisfaction consistently normalized by 1 year.…”
Section: A Second Nonsurgical Treatment or Surgery Ismentioning
confidence: 90%
See 1 more Smart Citation
“…Both findings were supported in some of the prospective studies conducted comparing the two techniques 21,26 but not in others. [22][23][24][25] No difference in return to work data was found in some studies 23,24 despite greater short-term pain in the ECTR groups. Differences in symptom severity scores, functional status, and satisfaction consistently normalized by 1 year.…”
Section: A Second Nonsurgical Treatment or Surgery Ismentioning
confidence: 90%
“…In an attempt to resolve this issue, numerous prospective randomized trials have been reported comparing ECTR to OCTR. [21][22][23][24][25] The most consistent arguments made in favor of ECTR have been less postoperative pain than OCTR and a shorter return to functional activities, particularly preoperative work status. Both findings were supported in some of the prospective studies conducted comparing the two techniques 21,26 but not in others.…”
Section: A Second Nonsurgical Treatment or Surgery Ismentioning
confidence: 99%
“…9,16 -20 These differences were found to normalize at 1 year. [21][22][23] Endoscopic carpal tunnel release has become an accepted treatment alternative to OCTR. Even in light of the above data, concern has been expressed that results of ECTR are limited by the surgeon's experience.…”
mentioning
confidence: 99%
“…The other eight studies found no difference between groups 9−13,15 −17) . Five of the reports 9,13,14,16,17) des cribed improvements in sensation, but no significant differences were seen in any of the studies. Three reports 9,10,16) described electrophysiological findings, also without any significant difference.…”
Section: Discussionmentioning
confidence: 89%
“…In the ECTR group, surgery was performed without a tourniquet according to the methods of Okutsu et al 13) . In the OCTR group, tourniquets were used with all patients and a 3 -cm vertical incision was made in the palm (Fig.…”
Section: Surgical Procedures and Postoperative Protocolmentioning
confidence: 99%